Dynamics of Selected Serum Immunological Markers During Caesarean Section - Pešková, Klára; Štourač, Petr; Seidlová, Dagmar; Hruban, Lukáš; Hurdálková, Karolína (Neuro-endocrinology letters, 2021)
OBJECTIVES: The presented study aimed to describe the dynamics of the serum levels of the complement components C3, C4, and C1 inhibitor in women immediately before and after giving birth by caesarean section (CS). DESIGN AND SETTING: 57 pregnant women undergoing caesarean section were included in this prospective observational study. Blood samples were taken 30 minutes before CS and 30 minutes after the delivery. C3, C4, and C1 inhibitor levels were analysed and the functional C1 inhibitor test performed. Angiotensin-converting enzyme concentrations before delivery were also determined. RESULTS: Before delivery, C3 value was elevated above the reference limits for the healthy adult population in 39% of patients. Following birth, C3 median value dropped from 1.4 to 1.2 g/L. C1 inhibitor concentrations were also reduced - the median value of the C1 inhibitor before the birth was 222 mg/L, dropping to 198 mg/L after delivery. Even before the CS, C1 inhibitor concentrations were below reference range in 40% of patients, which increased to 56% after delivery; its activity however did not significantly change. In two patients with perioperative uterine hypotonia, notable complement activation was detected. ACE levels were below the normative values for adult population in 25% of patients. CONCLUSION: Concentrations of all analysed components significantly decreased after delivery, which was not associated with blood loss or amount of intravenous liquids. This highlights the necessity of proper reporting of the time point of blood sampling in any studies or case reports detailing the immunological condition of patients in the peripartal period.
Keywords: Pregnancy; těhotenství; Adult; biologické markery; Prospective Studies; dospělí; lidé; Female; ženské pohlaví; císařský řez; Humans; Biomarkers; Cesarean Section; prospektivní studie